Protecting the Rights of People with Autism in the Fields of Education and Employment: International, European and National Perspectives - Della Fina, Valentina (Springer, 2016)
Fundamental rights for all people with disabilities, education and employment are key for the inclusion of people with autism. They play as facilitators for the social inclusion of persons with autism and as multipliers for their enjoyment of other fundamental rights. After outlining the international and European dimensions of the legal protection of the rights to education and employment of people with autism, the book provides an in-depth analysis of domestic legislative, judicial and administrative practice of the EU Member States in these fields. Each chapter identifies the good practices on inclusive education and employment of people with autism consistent with principles and obligations enshrined in the UN Convention on the Rights of Persons with Disabilities (Articles 24 and 27).